Manajemen Proyek Sistem Informasi Penyimpanan Laporan Keuangan Pada Kantor Badan Keuangan Dan Aset Daerah Provinsi Sumatera Utara - Muhammad Raihan Ath Thotiq; Yahfizham Yahfizham (Router : Jurnal Teknik Informatika dan Terapan, 2024)
The Regional Asset Management Agency (BKAD) of North Sumatra Province still uses a manual file management system for financial reports, namely by using physical folders. This system is considered to be ineffective and inefficient, and has a high risk of file damage or loss. This can lead to delays in the preparation of financial reports. This study aims to design a computerized file management information system for financial reports. This system is expected to improve the effectiveness, efficiency, transparency, and accountability of financial file management in BKAD. This system is designed using a structured database to store financial file information. Stakeholders can easily find the information they need through this system.